Interplay Between Grip and Vision in the Monkey Medial Parietal Lobe. (3rd May 2017) - Breveglieri, Rossella; De Vitis, Marina; Bosco, Annalisa; Galletti, Claudio; Fattori, Patrizia
Abstract: We aimed at understanding the relative contribution of visual information and hand shaping to the neuronal activity of medial posterior parietal area V6A, a newly added area in the monkey cortical grasping circuit. Two Macaca fascicularis performed a Reach-to-Grasp task in the dark and in the light, grasping objects of different shapes. We found that V6A contains Visual cells, activated only during grasping in the light; Motor neurons, equally activated during grasping in the dark and in the light; Visuomotor cells, differently activated while grasping in the dark and in the light. Visual, Motor, and Visuomotor neurons were moderately or highly selective during grasping, whereas they reduced their selectivity during object observation without performing grasping. The use of the same experimental design employed in the dorsolateral grasping area AIP by other authors allowed us to compare the grasp-related properties of V6A and AIP. From these data and from the literature a frame emerges with many similarities between medial grasping area V6A and lateral grasping area AIP: both areas update and control prehension, with V6A less sensitive than AIP to fine visual details of the objects to be grasped, but more involved in coordinating reaching and grasping.